God, emperor worship and society - Botha, P. J. J. (1988)
This paper discusses and explains some aspects of emperor worship. Two limitations in terms of evidence are observed by focussing on the cities mentioned in Revelation 1-3 and remaining within the first century. Emperor worship was a very important way of conceptualising reality, that is society and politics under Roman rule. More fundamentally it reflected a certain perspective on God. These two facets explain something of the conflict experienced by contemporary society and some Christian groups at the end of the first century in Asia Minor.
Keywords: imperial cult; Experiences of the divine; Emperor Worship; New Testament Bible; Church History; Theology; Christianity; Revelation